Using Pop-up Pictures to Improve the Eighth Grade Students’ Vocabulary - Suharjito, Bambang; Wijayanti, Sheila; Sukmaantara, I Putu (EFL Education Journal, 2016)
This Classroom Action Research was intended to improve the VIII-C students’ participation and vocabulary achievement by using Pop-up Pictures at SMPN 1 Beji - Pasuruan. The research area was chosen by using purposive method. The data collection methods of this research were interview, observation, documentation, and vocabulary achievement test. The research participants were VIII-C students. This research was held collaboratively between the researcher and the English teacher. The research was done in two cycles while each cycle consisted of three meetings. The observation result in Cycle 1 showed that the average of the students’ participation was only 65%. It increased to 77.5% the observation result in Cycle 2. Additionally, there were only 65% students who got score 70 in Cycle 1 and it was 77.5% students got score 70 or higher in the vocabulary achievement test in Cycle 2. It means that the objectives of the research were successful. Keywords: Pop-up Pictures, Students' Participation, Students' Vocabulary